Corporate Identity: Developing Means for Sustainable Competitive Advantage in Indian Context Towards Model Development - Jain, Varsha; Paul, Niriksha; B. E., Ganesh; Chauhan, Dhruvinkumar (Organizations and Markets in Emerging Economies, 2016)
Corporate identity is a dynamic and premeditated asset integral to gaining competitive advantage in the market. It spans both the internal and external functions of the organisations. It is a variable that needs to be studied cohesively. However, the literature on corporate identity has studied the various elements in a non integrated manner. This needs to be replaced by a comprehensive understanding of the processes and nuances of corporate identity, which can help the organisations in developing sustainable competitive advantage. Additionally, this study focuses on digital media and tech savvy individuals from an emerging market: India. In order to achieve this objective, we interviewed 70 respondents from 20 companies and their consumers. Thus, we identified that corporate identity deals with strategic, emotional and social dimensions. This helped us develop a comprehensive model. Further, corporate identity was seen as a benchmark related to corporate challenges and expectations. Lastly, digital media need to work as a bonding platform among the stakeholders to ensure this.
Keywords: corporate identity; sustainable competitive advantage; digital bonding platform; internal and external stakeholder; India